Uji Antibakteri Ekstrak Etanol Daun Theobroma cacao L. terhadap Pertumbuhan Escherichia coli dengan Metode Difusi Cakram - Annisa Rahmi Hayati; Abdul Rahman Singkam; Dewi Jumiarni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the inhibition of T. cacao L. leaf extract on the growth of E. coli bacteria and the correlation between the concentration of T. cacao L. leaf extract and the formed E. coli inhibition zone. The method used is experimental post-test only control design using Completely Randomized Design (CRD). The inhibition zone of T. cacao L. leaves against E. coli was tested using the disc diffusion method with six treatments (concentration 25%, 50%, 75%, 100%, positive control and negative control) repeated five times. The results showed that the diameter of the inhibition zone of the leaf extract of T. cacao L. against E.coli was at intervals of 5-10 mm and was included in the category of moderate inhibition, but the results of Duncan's test showed that there was no significant difference between the inhibition zones formed at concentrations 25%, 50%, 75%, and 100%. In conclusion, the leaves of T. cacao L. were less effective in inhibiting the growth of E. Coli, but the leaf extract of T. cacao L. was positively correlated with the inhibition zone formed. Keywords: Leaf Extract, Escherichia coli, Theobroma cacao L., Zone of Inhibition Test